Exploring affordability and healthcare-seeking behaviour for delivery and antenatal care among the poor and ethnic minorities in rural Northwestern Viet Nam. Issue 1 (1st January 2019) - Matsubara, Chieko; Nguyen, Tai Anh; Murakami, Hitoshi
ABSTRACT: Background : Health insurance (HI) has been introduced to achieve universal health coverage. In Viet Nam, mandatory HI for the poor and the minorities has been strengthened since 2012. Objective : The study explored affordability and healthcare-seeking behaviour for delivery and antenatal care (ANC) among the poor and ethnic minority women after HI-reform in rural Northwestern Viet Nam. Methods : A cross-sectional study was conducted in 2014 in Luong Son District, where the ethnic Muong live. Stratified simple random sampling was used to select 315 participants who had delivered a baby in the previous year. Results : The HI coverage was 72.7% (229/315) and 30.9% of the mothers were living on less than USD 1.25 per household person per day. HI enrolment was predicted by ethnic minority status (Muong, aOR 18.3, 95% CI 6.4–52.6), rather than the household income. More than 80% of majority and minority respondents selected the institution by their trust in the quality of its care. The institutional delivery was 100%, irrespective of HI status. The out-of-pocket expenses for normal delivery were significantly smaller for the insured than the uninsured (p < 0.001). The total cost of normal delivery proved to be a catastrophic payment (households spending > 5% of annual household income) for 17.6% and 31.7% of the insured and uninsured, respectively. The average number of ANC visits was more than four times for all quartiles, irrespective of the mothers' HI status; however, all quartiles demonstrated more frequent visits to private clinics than commune health centres (public facility). Conclusions : The results indicated that Vietnamese HI reform reduced the economic burden for both the poor and ethnic minorities in rural villages. However, further HI reforms should consider ways to reduce the catastrophic payments, fix the role of private facilities for appropriate resource mobilisation, and enhance the move towards universal health coverage.